Strategies for Teaching Arabic through the Use of Technology and Mass Media - Khalid Yusuf Al-Misri; Dicky Zulkarnain (IJAS: International Journal of Arabic Studies, 2026)
This study examines strategies for teaching Arabic through the integration of technology and mass media in contemporary educational contexts. Using a qualitative case study approach, the research explores how digital tools and media resources are utilized to enhance the learning process. Data were collected through interviews, observations, and documentation involving teachers and students. The findings indicate that the use of technology and mass media significantly improves students’ motivation, comprehension, and communicative competence. Additionally, it promotes learner autonomy and provides exposure to authentic language and cultural contexts. However, challenges such as limited infrastructure, lack of teacher training, and the need for balanced implementation remain critical issues. The study concludes that effective integration of technology and mass media requires strategic planning, institutional support, and continuous professional development to optimize Arabic language teaching in the digital era.